The impact of intravenous immunoglobulin therapy on resource utilization associated with viral respiratory tract infections - Azar, Antoine; Runken, M. Chris; Moughames, Eric; Howden, Reuben; Oh, Joshua; Blanchette, Christopher M. (Frontiers in Immunology, 2025)
IntroductionImmunocompromised patients with moderate to severe viral respiratory tract infections (VRTIs) may benefit from intravenous immune globulin (IVIG) in combination with antivirals. The impact of this therapy on hospital resource utilization is unknown. The purpose of this study was to assess clinical outcomes and hospital resource utilization associated with IVIG use in immunocompromised patients hospitalized with VRTIs.MethodsUsing the Premier Healthcare Database, data from 1,927 inpatients with immune deficiency and acute VRTI were analyzed. Outcomes included measures relevant to hospital resource use and patient death rates. Descriptive statistics were used to measure factors associated with IVIG use across the hospital stay. A logistic regression model adjusted for factors associated with the probability of IVIG use within 48 hours of admission. The propensity score was used to weigh subsequent models to assess the length of stay (total and ICU) using a negative binomial model and logistical regression for inpatient death.ResultsOf the 1,927 patients analyzed, 65 received IVIG. When adjusting for IVIG use within 48 hours of admission and other patient and hospital characteristics, findings showed a significantly shorter hospital length of stay for patients with acute VRTIs when IVIG was given (p = 0.027). The length of ICU stay was also significantly shorter with IVIG use (p = 0.003).DiscussionImmunocompromised patients with VRTIs who receive IVIG within 48 hours of ICU admission may have a shorter ICU length of stay and shorter overall hospital length of stay thereby possibly decreasing healthcare resource use.